Descriptive Study to Evaluate Attitudes Toward Teenage Pregnancy Among Nursing Students in a Selected College in Virudhunagar - M. Manimehalai; R. Sangeetha (International Journal of Midwifery Nursing And Practices, 2024)
This study aimed to explore the attitudes of nursing students toward teenage pregnancy, focusing on a specific college in Virudhunagar. A purposive sampling technique was employed to select 50 participants using non-probability sampling methods. Data were gathered through a structured questionnaire based on a 5-point Likert scale, comprising 10 statements with response options ranging from "strongly disagree" to "strongly agree." The data collected were systematically organized, tabulated, and analyzed using descriptive statistical methods to identify trends in student attitudes. The results indicated that a majority of participants exhibited either a neutral or favorable stance toward teenage pregnancy. Specifically, 46% of the respondents had a favorable attitude, while 54% held a neutral perspective. Notably, none of the participants expressed an unfavorable attitude toward teenage pregnancy. This suggests that the nursing students in this study were generally open-minded or indifferent to the topic, with no strong negative views being expressed. The findings of this study highlight the need for targeted educational interventions to further understand and address the factors influencing students' attitudes toward teenage pregnancy. Further research is recommended to explore how these attitudes might impact nursing practice and the care of adolescent patients. Additionally, expanding the sample size and including other institutions could provide a more comprehensive view of nursing students' perspectives on this important issue.
Keywords: Pregnancy; Students; attitude; teenage; teenage pregnancy